Production of Brake Pad from Epoxy Resin: From Polymerization Concept to the Experiment with Analysis of Mechanical Properties - Nandiyanto, Asep Bayu Dani; Fiandini, Meli; Al Husaeni, Dwi Novia; Ragadhita, Risti; Hofifah, Siti Nur (Jurnal Penelitian Enjiniring, 2021)
The purpose of this study was to determine the effect of variations in the use of catalysts on the performance of brake pads. The performance testing is compressive strength and puncture strength. The resin is formed from a mixture of Bisphenol A-epichlorohydrin and cycloaliphatic amine. Based on the results of the study, it was found that brake pads with samples B and C had better performance. The hardness values of samples A, B, and C are 307.4; 331.1; and 334.3 N, respectively. The ratio of resin and catalyst mixture affects the performance of the brake pad. The more catalysts added, the faster the hardening process. It is hoped that this research can be the basis for developing brake pads.